Automatic Quantification of Microvessels Using Unsupervised Image Analysis - Petter Ranefall; Kenneth Wester; Christer Busch; Per-Uno Malmström; Ewert Bengtsson (Analytical Cellular Pathology)
An automatic method for quantification of images of microvessels by computing area proportions and number of objects is presented. The objects are segmented from the background using dynamic thresholding of the average component size histogram.